0470 A Randomized Controlled Trial of Digital Cognitive Behavioral Therapy for Insomnia in Pregnant Women. (27th May 2020) - Kalmbach, D A; Cuamatzi-Castelan, A; Tonnu, C V; Roth, T; Sangha, R; Swanson, L M; O'Brien, L M; Drake, C L
Abstract: Introduction: Over half of pregnant women experience clinical insomnia, which is linked to perinatal depression and cognitive-emotional dysregulation. Despite high rates of prenatal insomnia and known maternal consequences, efficacious insomnia treatment options for this population are woefully scant. Early evidence from randomized controlled trials (RCTs) support the efficacy of face-to-face cognitive-behavioral therapy for insomnia (CBTI) for prenatal insomnia. Yet, as many patients are unable to access this specialist-driven care, a critical need exists to increase its accessibility. This RCT examined the efficacy digital CBTI via mobile health app in pregnant women with insomnia. Methods: Single-site RCT. Ninety-one pregnant women (29.03±4.16 years) nearing/entering the third trimester who screened positive for clinical insomnia on the Insomnia Severity Index (ISI) were randomized to digital CBTI or digital sleep education control. Blinded assessments were performed before treatment, after treatment (during pregnancy), and 6 weeks after childbirth. The ISI, Pittsburgh Sleep Quality Index (PSQI), Edinburgh Postnatal Depression Scale (EPDS), and Pre-Sleep Arousal Scale's Cognitive factor (PSAS-C) served as study outcomes. Results: From pre to posttreatment, CBTI patients reported reductions in ISI (-4.91 points, p<.001) and PSQI (-2.98 points, p<.001) and increases in nightly sleep duration by 32 minutes. Sleep symptoms did not change during pregnancy in the control group. After childbirth, CBTI patients, relative to controls, slept longer by 40 minutes per night (p=.01) and reported better sleep maintenance. No pre or postnatal treatment effects on depression or cognitive arousal were observed. Conclusion: Digital CBTI improves sleep quality and increases sleep duration during pregnancy and after childbirth. Digitally delivered interventions have potential to improve the health of new and expectant mothers, but CBTI likely needs to be tailored for perinatal patients to optimize outcomes. Support: This study was funded by the American Academy of Sleep Medicine (198-FP-18, PI: Kalmbach).